A study of validity and reliability for Subjective Global Nutritional Assessment in outpatient children with cerebral palsy. (2nd December 2022) - Peng, Tingting; Zhao, Yiting; Fu, Chaoqiong; Huang, Shiya; Zhou, Hongyu; Li, Jinling; Tang, Hongmei; He, Lu; Xu, Kaishou
ABSTRACT: Objectives: To investigate the reproducibility, stability, internal consistency and the ability to grade malnutrition of Subjective Global Nutritional Assessment (SGNA) in outpatient children with cerebral palsy. Methods: This was a part of a larger, cross-sectional study (ChiCTR2000033869) at the outpatient of a tertiary hospital. The recruitment and data collection of children with Cerebral Palsy aged from 1 to 18 years were from August 2020 to March 2021. The concurrent validity, inter-rater reliability, test–retest reliability and internal consistency of SGNA were tested. To analyze data, specificity, sensitivity, Kendall coefficient, Cohen's kappa coefficient, Spearman coefficient and Cronbach's α coefficient were used. Results: The agreement between SGNA and anthropometric data was moderate to strong ( k  = 0.540–0.821). The sensitivity (71.70% to 89.74%) and specificity (77.67% to 91.03%) of SGNA to identify participants with z -score ≤−2 were good. The sensitivity of SGNA to identify participants with weight for age z -score ≤−3 was poor (30.00%). The interrater reliability ( k  = 0.703) and test–retest reliability ( k  = 0.779) were good. The item of edema was with poor agreement to SGNA nutritional grades ( r s  = 0.072), and after deleting it from SGNA, the Cronbach's α coefficient of SGNA increased from 0.736 to 0.871. Findings: SGNA is good at identifying malnourished outpatient children with cerebral palsy, with excellent reproducibility and short-time stability. However, the ability to grade malnutrition is unsatisfactory. For further application in this group, a more appropriate item should be designed to replace the item of edema.